Anti-diabetic action of all-trans retinoic acid and the orphan G protein coupled receptor GPRC5C in pancreatic β-cells - Amisten, S; Mohammad Al-Amily, I; Soni, A; Hawkes, R; Atanes, P; Persaud, S; Rorsman, P; Salehi, A (Japan Endocrine Society, 2017)
Pancreatic islets express high levels of the orphan G-protein coupled receptor C5C (GPRC5C), the function of which remains to be established. Here we have examined the role of GPRC5C in the regulation of insulin secretion and β-cell survival and proliferation using human and mouse pancreatic islets. The expression of GPRC5C was analysed by RNA-sequencing, qPCR, western blotting and confocal microscopy. Insulin secretion and cell viability were determined by RIA and MTS assays, respectively. GPRC5C mRNA expression and protein level were reduced in the islets from type-2 diabetic donors. RNA sequencing in human islets revealed GPRC5C expression correlated with the expression of genes controlling apoptosis, cell survival and proliferation. A reduction in Gprc5c mRNA and protein expression was observed in islets isolated from old mice (>46 weeks of age) compared to that in islets from newborn (<3 weeks) mice. Down-regulation of Gprc5c led to both moderately reduced glucose-stimulated insulin release and also reduced cAMP content in mouse islets. Potentiation of glucose-stimulated insulin secretion concomitant with enhanced islet cAMP level by all-trans retinoic acid (ATRA) was attenuated upon Gprc5c-KD. ATRA also increased [Ca+2]i in Huh7-cells. Gprc5c over expression in Huh7 cells was associated with increased ERK1/2 activity. Gprc5c-KD in clonal MIN6c4 cells reduced cell proliferation and in murine islets increased apoptosis and the sensitivity of primary islet cells to a cocktail of pro-apoptotic cytokines. Our results demonstrate that agents activating GPRC5C represent a novel modality for the treatment and/or prevention of diabetes by restoring and/or maintaining functional β-cell mass.